Thiasophila szujeckii sp. n. (Coleoptera, Staphylinidae, Aleocharinae)—a cryptic species associated with Formica truncorum in Poland - Zagaja, Mirosław; Staniec, Bernard (Zootaxa, 2015)
The article describes a new rove beetle species, Thiasophila szujeckii sp. n., in southeastern Poland. This new species is associated exclusively with Formica truncorum. The authors describe its sexual dimorphism of habitus, structure of antennae, eighth abdominal tergite and eighth sternite. T. szujeckii sp. n. shares most morphological features with T. angulata and T. lohsei known in Europe. Characters of adults which differentiate the new species from the above-mentioned ones include body size, coloration, structure of ligula, aedeagus, parameres and spermatheca. In order to confirm morphological distinctivness of T. angulata and T. szujeckii, mitochondrial cytochrome oxidase II gene (COII) partial sequences of both taxa was analyzed.